Strategi Persaudaraan Muslimah (Salimah) Deli Serdang Dalam Meningkatkan Kesadaraan Parenting Islami Di Kalangan Para Anggota - Rahma Dewi; Tengku Walisyah (Universitas Cokroaminoto Yogyakarta, 2025)
This descriptive qualitative research aims to analyze the strategy of the Muslim Brotherhood (Salimah) Deli Serdang in increasing awareness of Islamic Parenting among its members. Data were collected through documents, interviews and observations. The results of the study indicate that the strategies implemented by Salimah have a significant role in forming parenting patterns based on Islamic values. These strategies include organizing seminars, communication between members, joint visits with members and families, and a dialogue approach (Heart to Heart) between parents and children. The impact of implementing this strategy is seen in the increase in understanding and practice of Islamic Parenting among members, which contributes to the formation of children's characters who are more religious and have good morals. The challenges are the influence of technology, lack of parental awareness, an unsupportive environment, and limited time with family.